Developing a Profile of Procedural Expertise: A Simulation Study of Tracheal Intubation Using 3-Dimensional Motion Capture. Issue 4 (August 2020) - Kerrey, Benjamin T.; Boyd, Stephanie D.; Geis, Gary L.; MacPherson, Ryan P.; Cooper, Edward; Kiefer, Adam W.
Abstract : Background: Improving the assessment and training of tracheal intubation is hindered by the lack of a sufficiently validated profile of expertise. Although several studies have examined biomechanics of tracheal intubation, there are significant gaps in the literature. We used 3-dimensional motion capture to study pediatric providers performing simulated tracheal intubation to identify candidate kinematic variables for inclusion in an expert movement profile. Methods: Pediatric anesthesiologists (experienced) and pediatric residents (novices) were recruited from a pediatric institution to perform tracheal intubation on airway mannequins in a motion capture laboratory. Subjects performed 21 trials of tracheal intubation, 3 each of 7 combinations of laryngoscopic visualization (direct or indirect), blade type (straight or curved), and mannequin size (adult or pediatric). We used repeated measures analysis of variance to determine whether various kinematic variables (3-trial average for each participant) were associated with experience. Results: Eleven experienced and 15 novice providers performed 567 successful tracheal intubation attempts (9 attempts unsuccessful). For laryngoscopy, experienced providers exhibited shorter path length (total distance traveled by laryngoscope handle; 77.6 ± 26.0 cm versus 113.9 ± 53.7 cm; P = 0.013) and greater angular variability at the left wrist (7.4 degrees versus 5.5 degrees, P = 0.013) and the left elbow (10.1 degrees versus 7.6 degrees, P = 0.03). For intubation, experienced providers exhibited shorter path length of the right hand (mean = 61.1 cm versus 99.9 cm, P < 0.001), lower maximum acceleration of the right hand (0.19 versus 0.14 m/s 2, P = 0.033), and smaller angular, variability at the right elbow (9.7 degrees versus 7.9 degrees, P = 0.03). Conclusions: Our study and the available literature suggest specific kinematic variables for inclusion in an expert profile for tracheal intubation. Future studies should include a larger sample of practitioners, actual patients, and measures of the cognitive and affective components of expertise. Abstract : Supplemental digital content is available in the text.